The Holland Centre Experience : A Community Development Model for Minorities - Walling, Richard; Hanrahan, Louis; Johnson, Jennifer (Holland Resources Development Corporation, 2001)

AQ Holds a Press Conference on the Quebec Court of Appeal Decision in the Lyon and the Walrus - Alliance Quebec (AQ) (2001)

Commissioner of Official Languages Identifies Systemic Problems for English-speaking Canada Post Workers - Alliance Quebec (AQ) (2001)

AQ President Brent Tyler Urges the Review Committee to Respect the Rule of Law - Alliance Quebec (AQ) (2001)

The East Island Chapter of Alliance Quebec Passes a Resolution Supporting the Parents of Students Attending St Patrick Elementary in their Struggle to Save Quebec's First English School - Alliance Quebec (AQ) (2001)

Alliance Quebec Expressed its Profound Disappointment with Judge Maurice Legacé's Judgement - Bill 170 - Alliance Quebec (AQ) (2001)

AQ Announces Initiative Against Bill 171 - Alliance Quebec (AQ) (2001)

AQ Applauds OCOL's Intervention on Behalf of Minority Language Rights - Alliance Quebec (AQ) (2001)

Alliance Quebec Agrees with the Office of the Commissioner of Official Languages National Report on Service to the Public in English and French : Time for a Change in Culture - Alliance Quebec (AQ) (2001)

AQ Holds Press Conference to Announce AQ Initiatives to Ensure That Immigrant Children in French Schools, Who Are Two (2) or More Years Behind Their Peers, are Provided with an Opportunity to Receive A Proper Education - Alliance Quebec (AQ) (2001)

Alliance Quebec Representatives Brief MPs on Continuing Challenges Faced by the English-speaking Community - Alliance Quebec (AQ) (2001)

Alliance Quebec to Host Public Information Session on the MUHC - Alliance Quebec (AQ) (2001)

Alliance Quebec Demands a Future for English-speaking Quebecers - Alliance Quebec (AQ) (2001)

AQ Requests Meeting with Premier Landry - Alliance Quebec (AQ) (2001)

AQ Demands Fifth Riding in West Island - Alliance Quebec (AQ) (2001)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

AQ Dismayed that OLF Would Fine Municipalities for Having Generic English Word on Street Signs - Alliance Quebec (AQ) (2001)

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Alliance Quebec Shocked at PQ Government's Decision to Deny Quebecers Their Share of Federal Funding - Alliance Quebec (AQ) (2001)

Alliance Quebec News Magazine - Alliance Quebec (AQ) (2001)

Annual Report 2000-2001 - Alliance Quebec (AQ) (2001)

Communication and Efficiency : Language and Health Care Brief Presented to the Clair Commission - Alliance Quebec (AQ) (2001)
Alliance Quebec welcomes the opportunity to present the concerns of the English-speaking community during the public consultations on the reorganization of health care. As we all know, communication is fundamental to proper diagnosis and treatment of the patient. It also plays a vital role in ensuring a patient is comfortable with his or her health care professional. Alliance Quebec is of the opinion that no matter how fine and efficient a health care system is, it will be less effective if it cannot communicate effectively with the patient and vice versa.

Ike and Ifeoma Okwuobi Win Access to English School Case - Alliance Quebec (AQ) (2001)

Making Quebec Health Care User-Friendly (Again) - Hamelin, Michael J.; Bechervaise, Lynden; Goodwin, Robina; King, Maurice; Buckle, Scott; May, Bob; Jackson, Léon (2001)

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)